The narrative of Sound Horeg as Indonesian popular culture: A critical discourse analysis - Ahmad Rizky Wahyudi; Danang Wijoyanto; Sugeng Adipitoyo; Anas Ahmadi; Dandy Ashghor Dawudi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Current digital public spheres provide a new medium for one Indonesian grassroots community group to bring sound horeg as its local cultural expression into national discussions. From an opposing side, dominant discourses from formal authorities and mainstream media continuously frame the practice of sound horeg as a social threat. This condition raises the urgency to examine subcultural actors' strategies in negotiating stigma and seizing the cultural legitimacy of sound horeg within Indonesian society. Proceeding from this issue, this study examines sound horeg as Indonesian popular culture situated within public debates on noise, morality, and social order. The research aims to analyze sound horeg representation and its identity negotiation through Memed Potensio's narrative as a practitioner in the Aduan Masyarakat program on TrÃ¨tan Universe's YouTube channel. The qualitative descriptive method uses Norman Fairclough's Critical Discourse Analysis integrated with Stuart Hallâ€™s representation theory. Data obtained from the relevant episode's transcription were analyzed across textual, discourse practice, and sociocultural dimensions. The study concludes that sound horeg discourse in digital media spaces operates as a counter-practice resisting dominant cultural hegemony. Subcultural actors successfully deconstruct negative stigmas like 'illegal', 'immoral', and 'tacky' labels attached by formal authorities and urbanites. This discursive practice strategically shifts sound horeg from a mere social disturbance into a manifestation of collective identity legitimacy, communal solidarity, and cultural sovereignty for grassroots communities and the local working class. Theoretically, this research expands the application of critical discourse analysis to Indonesian local popular culture phenomena.